To combine these fractions, we need to find a common denominator. The common denominator here is 9x * 7x.
The first fraction can be rewritten as (2/9x) * (7x/7x) = 14x/63x^2.
The second fraction can be rewritten as (1/7x) * (9x/9x) = 9x/63x^2.
Adding the fractions together, (14x/63x^2) + (9x/63x^2) = (14x + 9x) / 63x^2 = 23x / 63x^2.
To reduce this fraction, we can simplify the numerator and denominator.
23x can be factored into 23 * x.
63x^2 can be factored into 9 * 7 * x * x.
So, the fully reduced fraction is 23x / 63x^2 = (23 * x) / (9 * 7 * x * x) = 23 / (9 * 7 * x) = 23 / (63x).
Combine the following fractions and express in fully reduced form.
start fraction, 2, divided by, 9, x, end fraction, plus, start fraction, 1, divided by, 7, x, end fraction
9x
2
+
7x
1
1 answer